Introductory sociology and anthropology : a pedagogy - Javier, Jessie D.; Costales, Rodrigo D.;Rivas, Dionesio C. (Manila, Philippines : Rex Book Store, 2002)
Sociology and Anthropology, two distinctive bodies of knowledge that interact with each other, two forces that hold all that we need to know in our never ending quest for a much deeper study of man and his society. Like a whirlpool, it meets continuously at the center and as man from there we must be alone.
CHAPTER 1. Sociological and Anthropological Imagination: Genesis, Development, and Forerunners -- 2. Methodological Considerations in Contemporary Sociology -- 3. Culture: Humankind's Imprints to Civilization -- 4. Courtship, Marriage, Family, Family Planning, Dissolution of Marriage, and Abortion -- 5. Politics, Power, State, and Government -- 6. Education: Objectives, Philosophy, and History -- 7. Economic Institution -- 8. Deviance, Crime, and Social Control -- 9. Personality and Socialization -- 10. Social Groups, Stratification, and Organizations -- 11. Population and Demography -- Bibliography -- Suggested Syllabus on Sociology and Anthropology
Includes bibliographical references.
Keywords: SOCIOLOGY